Respuesta :

The answer to your question is -9 + 9i

Answer:

Value of [tex](-7+3i)-(2-6i)= -9 + 9i[/tex]

Step-by-step explanation:

To find the value of the give expression: [tex](-7+3i)-(2-6i)[/tex]

Property of subtraction of complex number states that the subtract [tex]z_1-z_2[/tex]  of two complex numbers [tex]z_1 = a+ib[/tex] and [tex]z_2= c+id[/tex]  is defined as the complex number  i.e  

[tex]z_1 -z_2 = (a+ib)-(c+id) =(a-c) +i(b-d)[/tex]

It is observed that while subtracting two complex numbers the real and imaginary parts of the system is obtained by subtracting the real and imaginary parts of the summands.

Now;

[tex](-7+3i)-(2-6i) = (-7-2) +(3-(-6))i = -9 + (3+6)i = -9+9i[/tex]

Therefore, the value of [tex](-7+3i)-(2-6i)[/tex] is, -9 + 9i.